Enhancing ICT-based international interactions: Impact of Zoom and Padlet on willingness to communicate, international posture, and speaking proficiency - Sho Kobayashi (Technology in Language Teaching & Learning, 2024)
This study explores the affective aspects ― Willingness to communicate (WTC) and International Posture (IP) ― and speaking skills after using technological tools. Online synchronous meeting tool, Zoom, and the asynchronous tool, Padlet, were used as online learning platforms. Data were collected using an 8-item questionnaire on the WTC and a 20-item questionnaire on IP. They were pre-existing questionnaires developed for the Japanese context and were administered to 34 college students before and after their lessons. Participants’ speaking ability was tested twice (pre- and post-tests). Open-ended responses and participant reflections were also analyzed to gain further insights. Results showed significant effects on enhancing WTC, IP and speaking skills of participants with regard to ICT-based International Interactions. In addition, positive communication experiences with cross-cultural partners using Zoom and Padlet led to higher affective aspects and learning motivation. The findings suggest the viability of Padlet and Zoom as a tool for all proficient learners because of their relative ease of use and data management features. The implication of this study is relevant to a pedagogical tool in online exchanges for the current generation of students.